Synthesis and Anticonvulsant Activity of Some Novel Semicarbazone Containing Benzoxazole: Pharmacophore Model Study - Deshmukh, Ravitas; Thakur, Alok S.; Jha, Arvind K.; Kumar, Sudhir P. (Current Bioactive Compounds, 2018)
Background: Epilepsy is a common neurological disorder characterized by recurrent unprovoked seizures. Approximately 60 million people worldwide suffer from epilepsy, making this condition the second leading neurological disorder. Epilepsy also affects about 4% of individuals over their lifetime. The most commonly used anticonvulsant drugs are associated with numerous side effects including ataxia, hepatotoxicity and megaloblastic anemia. This review aims that there is a vast requirement for the development of drugs which is more effective and having safer antiepileptic properties. Method: 5-Chloro-2(3H)-benzoxazolone(i) was synthesized by the reaction of 2-amino-4- chlorophenol and urea in concentrated HCl at 140-180°C. Compound i reacted with 1,4-diamine and reflux it for 1hr in the presence of methanol and glacial acetic acid to get the compound ii. This compound was then treated with sodium cyanate in the presence of glacial acetic acid to get the urea derivative of the compound i.e. compound iii, then the compound iii was reacted with hydrazine hydrate to get the compound iv, then these compound was converted to semicarbazones by condensing it with an aryl/alkyl aldehyde & ketone in the presence of ethanol & glacial acetic acid. Results: In the electroshock method, two compounds (Ve and Vl) were found extensively active as these compounds showed protection at the low dose of 30mg/kg after 0.5h. These compounds also showed the activity after 4.0h, but at the higher dose indicating that the compounds show rapid onset of action as well as the duration of action. Substitutions at the hydrophobic site showed that the compounds give better activity. The substitutions are done at the para position of the hydrophobic aryl ring with the electron withdrawing groups. In the ScPTZ model, compounds showed good anticonvulsant activity, compounds that showed protection at 100mg/kg after 0.5h wereVd, Ve, Vh, Vk and Vl. Among these compounds, Ve and Vlwere found to be active because these compounds showed the activity at the same dose after 4.0h. Conclusion: All the newly synthesized compounds were investigated for the anticonvulsant activity against maximal electroshock-induced seizures (MES) and subcutaneous Pentylenetetrazole (scPTZ) models and their neurotoxicity was also evaluated by the rotarod test. Most of the compounds were found active in the biological screening. The results of the present study confirmed the requirementsof various structural features of four binding site pharmacophore model for anticonvulsant activity.
Keywords: benzoxazole